Analysis of voltage distribution in electrowetting on Dielectric (EWOD) system. (2021) - Khanna, Mansi; Roy, Souradeep; Mathur, Ashish; Dubey, Ashwani Kumar; Vashisth, Rashmi
Abstract: Electrowetting on Dielectric (EWOD) is one of the most popular digital microfluidic techniques, deployed in Lab-on-a-Chip (LoC) systems for analyzing samples of biomedical relevance. Despite the popularity of EWOD for testing of biochemical and biomedical samples, the technique faces two major challenges: preserving the cells of biosample and electrodes due to the application of high voltage and ensuring the droplets stay on tracks in the electrode system. A detailed study of the electrostatic properties like capacitance and distribution of voltage for EWOD systems has not been performed till date, which otherwise may prove fruitful in designing future LoC platforms for efficient sampling and analysis. Therefore for effective study of digital micro fluidic devices, accurate value of potential difference with variation in dielectric layer of EWOD can be helpful. In the current paper, potential distribution around the sample is analyzed by carrying out voltage analysis of the droplet using COMSOL. Comparative analysis of effect of the three dielectric materials on EWOD was performed by comparing the voltage drop across the dielectric layer. Since thickness and nature of dielectric material governs the operational voltage of EWOD system, comparative study of voltage drop of the device was done for promising dielectric materials like PDMS, PMMA and SiO2 for dielectric thickness of 10 μm, 20 μm, 30 μm, 40 μm and 50 μm. The capacitance for all the respective design parameters was also evaluated using COMSOL. Young Lipmann's equation was used to establish the validity of the results. The dependency of EWOD system on electrolyte conductivity was also studied for NaCl solution for concentrations varying from 0.43 mM to 100 mM. The capacitance study of all the electrolyte concentration was performed as well to identify the electrolyte change.